Safety evaluation of Fy Protein™ (Nutritional Fungi Protein), a macroingredient for human consumption. (August 2022) - Furey, Brian; Slingerland, Kathleen; Bauter, Mark R.; Dunn, Celeste; Goodman, Richard E.; Koo, Sophia
Abstract: Fy Protein™ (Nutritional Fungi Protein) is a macro-ingredient produced from the fermentation of the fungal microorganism Fusarium strain flavolapis, isolated from springs in Yellowstone National Park. Fy Protein contains all of the essential amino acids plus fiber, fat, carbohydrates, vitamins, and minerals and is developed as an alternative to animal-based protein foods such as meat and dairy. Fy Protein's nutritional, digestibility, genotoxicity, allergenicity, toxicity, secondary metabolites, and pathogenicity were evaluated. Fy Protein did not show mutagenic or genotoxic potential in in vitro tests. In an allergenicity review, Fy Protein was found to be of low allergenic potential. In a 90-day sub chronic dietary study in rats, administration of Fy Protein did not produce any significant toxicologic manifestations, and the no observed effect level (NOAEL) was the highest-level fed of 150, 000 ppm (15% in the diet). Regulated secondary metabolites from fungi (termed mycotoxins) were non-detectable and below regulated levels using quantitative analytical techniques. A literature review was completed to identify the potential human pathogenicity of Fusarium sp., showing that Fusarium rarely infects humans, with infections seldom developing even in immunocompromised individuals. The results of these studies confirm that Fy Protein from fermented F. str. flavolapis has low toxicological, genotoxic, pathogenic, and allergenic potential under the conditions tested and anticipated use. Graphical abstract: Image 1